(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Voice recognition is one of the key evolutions of biometric identification system which notonly have identification capability but this technology can be used to create more sophisticatedapplications. This paper reviews the methodology for extracting features from speech signal. In thispaper we have discussed the Components of ASR and Mel Frequency Cepstral CoefficientMFCC,Distance Measurement with Automatic Speech Recognition System(ASR)